2004
DOI: 10.1002/cncr.20230
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of chemotherapy‐induced nausea and emesis after modern antiemetics

Abstract: BACKGROUNDThe authors determined the incidence of acute and delayed chemotherapy‐induced nausea and emesis (vomiting) (CINV) among patients receiving highly (HEC) or moderately (MEC) emetogenic chemotherapy. They also assessed whether physicians and nurses accurately recognized the incidence of acute and delayed CINV in their own practices.METHODSA prospective, observational study of adult patients receiving HEC or MEC for the first time was performed. Before patient enrollment, medical oncologists and oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
284
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(308 citation statements)
references
References 15 publications
(12 reference statements)
15
284
2
5
Order By: Relevance
“…Studies of antiemetic control rates that combine dissimilar emetogenic regimens together to report overall success rates may not be a valid means of describing actual rates of nausea and emesis control in clinical practice. 10,16,17 This heterogeneity in antiemetic response among different chemotherapy regimens indicates the need for quality improvements and may guide clinicians to focus research on chemotherapy regimens for which antiemetic therapy is inadequate. Potential future studies that can be derived from this research include targeting certain chemotherapy regimens to test newer antiemetic agents (e.g., aprepitant) in children, redefining and/or combining the acute and delayed phases for antiemetic studies in children who receive chemotherapy, and conducting studies to examine markers of chemotherapy-induced nausea and emesis that may predict the heterogeneity in response for children of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of antiemetic control rates that combine dissimilar emetogenic regimens together to report overall success rates may not be a valid means of describing actual rates of nausea and emesis control in clinical practice. 10,16,17 This heterogeneity in antiemetic response among different chemotherapy regimens indicates the need for quality improvements and may guide clinicians to focus research on chemotherapy regimens for which antiemetic therapy is inadequate. Potential future studies that can be derived from this research include targeting certain chemotherapy regimens to test newer antiemetic agents (e.g., aprepitant) in children, redefining and/or combining the acute and delayed phases for antiemetic studies in children who receive chemotherapy, and conducting studies to examine markers of chemotherapy-induced nausea and emesis that may predict the heterogeneity in response for children of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…Progress in preventing and controlling chemotherapy-induced vomiting has resulted in fewer patients experiencing vomiting during chemotherapy, whereas nausea continues to be reported by a majority of patients receiving emetogenic chemotherapy at some time during a course of treatments. 48 Compound/receptor signaling is key to initiating and controlling the emetic response. The most widely studied compound is serotonin, also known as 5-HT.…”
Section: Pathophysiology Of Nausea and Vomitingmentioning
confidence: 99%
“…With the development of national and international guidelines, the focus shifted from treatment to prevention through antiemetic prophylaxis [18]. Although CINV remains a concern, studies have shown that whereas the overall incidence of CINV was 83 percent in 1979 [19], the incidence of acute nausea was 35 percent just 25 years later [20]. The pharmaceutical industry's successful efforts had a profound impact on patients' quality of life and allowed many patients to complete chemotherapy regimens who previously would not have been able to do so [17].…”
Section: Potential Funding Sources For Mental Health Researchmentioning
confidence: 99%